SISTEM PENERIMAAN PEGAWAI DI FIF PT ASTRA KABUPATEN LAMONGAN DENGAN METODE FUZZY LOGIC TSUKAMOTO - Kemal Farouq Mauladi (Joutica, 2017)
Problems contained in a company that is the system of recruitment. Employee recruitment system is used to obtain employees who fit the characteristics of the company ASTRA OTOPARTS located in Lamongan. Therefore, the computer is one of the tools to meet the needs of companies in accelerating the process of determining the appropriate candidates to become employees of customer service or as an expert thus will facilitate the trainer to inform the number of candidates who pass the certificate and obtain a certificate of training to human resources development (HRD) . The method of fuzzy tsukamoto as decision-making of training outcome, which will give solution solution to trainer to overcome the existing problems with the result of data accuracy equal to 95% and eliminate the process of recruitment manually where determined by a manager and can minimize fraud in recruitment at FIF ASTRA OTOPART in Lamongan District.